Long-Term Contaminant Exposure Alters Functional Potential and Species Composition of Soil Bacterial Communities in Gulf Coast Prairies - Lumibao, Candice Y.; Liu, Yue (Microorganisms (Basel), 2024)
Environmental pollution is a persistent threat to coastal ecosystems worldwide, adversely affecting soil microbiota. Soil microbial communities perform critical functions in many coastal processes, yet they are increasingly subject to oil and heavy metal pollution. Here, we assessed how small-scale contamination by oil and heavy metal impacts the diversity and functional potential of native soil bacterial communities in the gulf coast prairie dunes of a barrier island in South Texas along the northern Gulf of Mexico. We analyzed the bacterial community structure and their predicted functional profiles according to contaminant history and examined linkages between species diversity and functional potential. Overall, contaminants altered bacterial community compositions without affecting richness, leading to strongly distinct bacterial communities that were accompanied by shifts in functional potential, i.e., changes in predicted metabolic pathways across oiled, metal, and uncontaminated environments. We also observed that exposure to different contaminants can either lead to strengthened or decoupled linkages between species diversity and functional potential. Taken together, these findings indicate that bacterial communities might recover their diversity levels after contaminant exposure, but with consequent shifts in community composition and function. Furthermore, the trajectory of bacterial communities can depend on the nature or type of disturbance.